Seminar Anti Bullying Menciptakan Ruang yang Aman Bagi Dunia Pendidikan: Analisis Kesejahteraan Psikososial Siswa di SMP Manggala Leles - Happy Yulia Anggraeni; Abdul Raziq; Aryan Gunadi; Elita Sri Rahayu; Fatimah Nurul Jannah; Gilang Angga (Pusat Riset dan Inovasi Nasional, 2025)
Bullying in schools significantly impacts students' psychosocial well-being, including decreased self-confidence, anxiety disorders, depression, and a desire to avoid school. This study aims to evaluate the effectiveness of a school-based anti-bullying program in reducing incidents of aggressive behavior among students at Manggala Middle School. This study used a qualitative approach, with data collection techniques through in-depth interviews with 10 teachers and 15 students as participants. In addition, researchers conducted direct observations of student activities and interactions in the school environment. The anti-bullying intervention program was implemented for one week and included several strategies, including counseling through seminars, the implementation of a strict school policy against all forms of bullying, and the involvement of the entire school community in creating a positive culture. One of the main principles of this policy is the consistent application of sanctions without discrimination, so that there is no room for tolerance for perpetrators of bullying. The results of the study indicate that Manggala Middle School has been committed and active in preventing and handling cases of bullying. Several efforts such as teacher patrols, student counseling, and monitoring of public spaces in the school have been carried out routinely. However, from observations and interviews, researchers found that there were still a number of students who did not realize that their actions were classified as bullying behavior, such as verbally teasing friends or excluding certain students from the group. Seeing this situation, the Community Service Program (KKN) participants from the Nusantara Islamic University (UNINUS) collaborated with the school to organize an anti-bullying seminar aimed at seventh and eighth grade students. This seminar aimed to increase students' awareness and understanding of the forms of bullying and their impact on victims. This program is expected to be the first step in creating a safe, comfortable, and violence-free learning space. Going forward, collaboration between schools, parents, and the community is expected to strengthen bullying prevention efforts on an ongoing basis.